Relationships between testosterone, cortisol and performance in professional cyclists - Hoogeveen, A. R.; Zonderland, M. L. (International Journal of Sports Medicine, 1996)
In the literature the use of plasma levels of cortisol and the testosterone and testosterone: cortisol ratio for training management is encouraged. Decreased levels of testosterone and increased levels of cortisol are suggested to be indicative for a disturbance in the anabolic-catabolic balance, which may express itself in decreased performance. The purpose of the study was to examine if the acute hormonal response to a bout of exercise and the resting levels of testosterone, luteinizing hormone (LH) and cortisol are correlated to performance in cyclists. In addition, the effect of training on this correlation was studied. Ten professional cyclists participated and measurements took place before and after a defined period of training. Maximum workload (Pmax), determined on a cycle-ergometer with a slowly increasing protocol, increased by 30 watt (p < 0.001). Workload at a lactate level of 4 mmol/l (P4) increased by 18 watt (p < 0.05). Post training, resting testosterone levels decreased from 28.8 +/- 74 nmol/l to 24.6 +/- 90 nmol/l (p < 0.05). Resting cortisol levels increased from 272 +/- 110 nmol/l pre training to 379 +/- 242 nmol/l post training (p < 0.05). These results indicate an increased catabolic state. The acute hormonal response and the resting levels of LH were not changed post training. The resting levels of testosterone and cortisol and the acute response to exercise showed no correlation with performance pre and post training. In spite of an increased catabolic state post training there was an increase in performance. These results suggest that in endurance trained cyclists, decreased testosterone levels, increased cortisol levels and a decreased testosterone: cortisol ratio does not automatically lead to a decrease in performance or a state of overtraining.